Application of dosimetry methods for internal organs exposure and possible influence to remote effects - Zhunussov, Y.T.; Zhumadilov, K.Sh.; Chaizhunusova, N.Zh.; Sayakenov, N.B.; Shabdarbaeva, D.M.; Gnyrya, V.S.; Аzimkhanov, А.S.; Stepanenko, V.F.; Fujimoto, N.; Shichijo, K.; Hoshi, M. (Publishing House of the KarSU named after academician E.A. Buketov, 2018)
Internal dosimetry study is conducted during rats exposure by dust of 56Mn powder during experiment to study exposure effect in Kurchatov reactor complex Baical-1 (Kurchatov city, East- Kazakhstan region). This study was performed by group of scientists from Japan, Kazakhstan, and Russian Federation. It was important to study effect of radiation, due to effect of possible influence to human, and effect of possible internal exposure because of close location to Semipalatinsk Nuclear Test Site and post effect of irradiation due to Hiroshima and Nagasaki atomic bomb, Chernobyl accident and others. It was comparison of data of two scenarios of rat irradiation: a) the experimental box was supplied with air filter only (targeted for animal’s breathing); b) the experimental box was supplied with the system of forced ventilation. After exposure to radioactive powder of 56Mn radioactivity in organs and tissues of the rats was measured. The result of assessments of internal doses from neutronactivated 56Mn in powder, sprayed over experimental animals was compared.
Keywords: internal exposure; Kurchatov; rats; organs; powder of 56Mn; samples